Unique variant of Adams–Oliver syndrome with dilated cardiomyopathy and heart block. Issue 4 (5th August 2013) - Atasoy, Halil Ibrahim; Tug, Esra; Yavuz, Taner; Cine, Naci
Abstract: Reported herein is the case of a 2‐year‐old boy with Adams–Oliver syndrome who presented with dilated cardiomyopathy and complete atrioventricular block. The patient had aplasia cutis congenita with partial aplasia of the skull bones, and terminal transverse limb malformations characteristic of the disease. Although congenital cardiac malformations may be associated with the syndrome, dilated cardiomyopathy has not been previously reported to be associated with the syndrome.